Digital Government and Open Data Readiness Assessment - World Bank (World Bank, Washington, DC, 2019)
This report, composed of two separate themes of Digital Government Readiness Assessment (DGRA) and Open Data Readiness Assessment (ODRA), is intended to help government assess their digital environments and frame their own strategies.In order to assess the potential for a Digital Enabling Government Initiative (DEGI) for Vietnam, this report compiles two chapters of aforementioned DGRA and ODRA. Specifically, it assesses potential opportunities and challenges of improving digital government and open data initiatives in the country. Although DGRA and ODRA are two separate assessments with different dimensions evaluated, they take a similar methodological approach from a broader point of view, starting with the desk research and later expanding to scoping mission. Therefore, both chapters of DGRA and ODRA are similar in format but outlined in respective assessment dimension and individual indicators. Since its onset in the fall of 2017, intensive desk research was conducted, and a field mission was carried out to confirm preliminary findings and uncover additional insight during a specific period in time, which means that during the course of analysis and writing additional developments could have been made. This is similar to the United Nations global e-government development report, which assesses progress during a “snapshot” in time.DGRA, the first part of the report, aims to evaluate Vietnam’s current potential for digital government development across seven key dimensions of leadership and governance; user focus; business process change; capabilities; culture and skills; shared infrastructure; data driven; and cybersecurity, privacy and resilience. Meanwhile, ODRA assesses Vietnam’s open data policy through evaluating eight different dimensions of leadership; policy/legal framework; institutional structure; data within government; demand; citizen engagement; funding; and infrastructure.The DGRA chapter focuses on digital government, which is a core part of Digital Economy as public sector delivers information and services more effectively and make them accessible to its citizens.The DGRA also measures the citizen’s demand for digital government services as well as integration and infrastructure policies to delve deeper into the opportunities and challenges the country faces in its digital development journey. The assessment includes a step-by-step analysis of specific components of digital government and presents an action plan to address the challenges identified for improvement.ODRA, the second part of the report, focuses on the country’s open data policy. Open data refers that the data must be both legally and technically open to public, thus placed in the public domain or under liberal terms of use with minimal restrictions, and that the data is published in machine-readable and preferably in non-proprietary electronic formats, which enables everyone to access and use data with freely available software tools.This report, bringing DGRA and ODRA assessments altogether, aims to help raise awareness of digital government and open data, two critical topics as Vietnam prepares its next step for the fourth industrial revolution (Industry 4.0). Further, it hopes to serve as a useful resource for the top government leadership in identifying areas of relative strengths and weaknesses to help improve digital government and open data at the same time.